Tempo and rhythmic abilities in female gymnasts as a factor of motor synchronicity in group gymnastic routines - Suprun, A.; Titova, A.; Borisova, V. (Human. Sport. Medicine, 2020)
Aim. The paper aims to justify the need to take into account the tempo and rhythmic abilities of female gymnasts as one of the factors of motor synchronicity in group gymnastic routines. Materials and methods. The study involved 12 highly skilled gymnasts aged from 18 to 19 years (Masters of Sport in rhythmic gymnastics). Two groups were formed based on gymnastic routines. Tempo and rhythmic abilities were assessed, and an expert evaluation of mistakes in motor synchronicity was carried out. Results. During the expert evaluation, the athletes made errors in the following components: unintended movements in start and final positions, lack of accuracy in positions and transitions, unity of routines and composition, where one follows from the other but is evaluated by different judges. It was also determined that the rhythmic pattern with the faster tempo was done more accurately than those with the slower tempo if it was simple. The rhythmic pattern such as eighth two sixteenth and three-beat dotted causes more difficulties when performed with inner counting (p ? 0.05). The strongest correlations between an expert evaluation of motor synchronicity and tempo and rhythmic abilities were found for the following rhythmic patterns: two-beat dotted, three-beat dotted, syncope (r = -0.524; r = -0.485; r = -0.545). Conclusion. The tempo and rhythmic abilities of gymnasts characterize the quality of motor synchronicity in group gymnastic routines, namely, the ability of gymnasts to implement the tempo and rhythmic structure of motor actions to music.